Análise da frequência anual das condições de céu em Botucatu, São Paulo - Teramoto, Érico T. [UNESP]; Escobedo, João F. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2012)
This paper presents an analysis of the frequency of the sky conditions in Botucatu. The classification of sky conditions was made based on the clearness index (K T), calculated from a database with 10 years of measured daily global solar radiation. Throughout the year in Botucatu, there is a predominance of days with clear sky condition, on average 114 days. For cloudy sky condition, the average frequency is 61 days. About the two intermediate sky conditions, the frequency of the sky partially cloudy with dominance for the diffuse is 94 days and the one with dominance for the clear is 96 days. The main influential factors on the sky conditions in Botucatu are the inputs of cold fronts and the formation of the South Atlantic Convergence Zone. They respond primarily by altering the sky condition of clear to cloudy or partially cloudy with dominance to diffuse. The aerosols resulting from burning in sugarcane fields respond by altering the sky condition from clear to partly cloudy with dominance for the clear.

Este trabalho apresenta uma análise da frequência das condições de céu em Botucatu. A classificação das condições de céu foi feita com base no índice de claridade (K T), calculado a partir de uma base de dados de 10 anos de radiação global diária. Em Botucatu há, ao longo do ano, predominância de dias com condição de céu claro, em média 114 dias. Para a condição de céu nebuloso a frequência média é de 61 dias e, em referência às duas condições de céu intermediárias, a frequência de céu parcialmente nebuloso com dominância para o difuso, é de 94 dias e a com dominância para o claro é de 96 dias. Os principais fatores influentes sobre as condições de céu em Botucatu são as entradas de frentes frias e a formação da Zona de Convergência do Atlântico Sul, as quais respondem principalmente pela alteração da condição de céu claro para a de céu nebuloso ou para a de céu parcialmente nebuloso com dominância para o difuso. Os aerossóis resultantes das queimadas em lavouras de cana-de-açúcar respondem pela alteração da condição de céu claro para a de céu parcialmente nebuloso com dominância para o claro.
Analysis of the annual frequency of the sky conditions in Botucatu, São Paulo
Keywords: solar radiation; cloudiness; clearness index; radiação solar; nebulosidade; índice de claridade